The effect of muscle stretching on the reduction of pain caused by Occupational Cervicobrachial Disorders (OCD) among mechanics at a Honda service workshop in Umbulharjo Yogyakarta - Zulhayudin, Muhammad Fadillah (Periodicals of Occupational Safety and Health, 2022)
Occupational Cervicobrachial Disorder (OCD) is a functional and/or organic disorder at the upper extremity due to neuromuscular fatigue caused by working activities at a fixed position or with repeated movements. The rate of musculoskeletal system disorder among mechanics in a number of countries has amounted to 76-92%. A preliminary survey using Nordic Body Map Questionnaire showed that the mechanics at a Honda workshop in Umbulharjo felt the work-related pain at the upper extremity. Therefore, intervention was deemed required to reduce such pain. Muscle stretching was selected as the intervention to be provided. This study is aimed at determining if muscle stretching has an effect on the reduction of OCD related pain among the mechanics at a Honda workshop in Umburharjo Yogyakarta. The study was quantitative in nature with quasi-experimental design. Based on cluster sampling technique with tracer survey methods, 30 samples were selected and divided into 2 groups, i.e., intervention group with 20 respondents and control group with 10 respondents. The measurement of pain scale was performed using Visual Analog Scale. The research results showed that there was significant reduction of pain scale upon the intervention of muscle stretching with the frequency of 6 times per week. Hence, the study comes up with a conclusion that muscle stretching has the effect on the reduction of pain caused by OCD among the mechanics at a Honda motorcycle workshop in Umbulharjo Yogyakarta.